Nivolumab‐Induced Thrombotic Thrombocytopenic Purpura in a Patient with Anal Squamous Cell Carcinoma: A Lesson on Hematologic Toxicity from Immunotherapy. (23rd October 2020) - Gergi, Mansour; Landry, Kara K.; Ades, Steven; Barry, Maura; Zakai, Neil A.; Herrera, Diego Adrianzen
Abstract: Thrombotic thrombocytopenic purpura (TTP) is a rare but life‐threatening microangiopathic hemolytic anemia characterized by thrombocytopenia, hemolytic anemia, and ischemic organ damage. It is mainly caused by an autoreactive antibody directed at ADAMTS13. Immunotherapy is frequently associated with autoimmune complications in patients with cancer, but only three cases of TTP have been reported, none implicating single treatment with the anti–programmed cell death receptor 1 ligand antibody nivolumab. We present the first identified and reported case of nivolumab‐associated TTP in a 51‐year‐old woman with stage IIIc anal carcinoma who achieved complete response following chemoradiation and received adjuvant nivolumab as part of a randomized clinical trial. Twelve weeks into treatment, she presented with dark urine, progressive fatigue, and headache. TTP diagnosis was based on laboratory evidence of hemolytic anemia, thrombocytopenia, and ADAMTS13 activity of 9% associated with an inhibitor. She was treated with daily plasma exchange and oral prednisone and responded well to treatment, with platelet counts over 100 K/cmm within 4 days. We reviewed and summarized data from all reported cases of TTP associated with cancer immunotherapy. We provide guidance on identification and management of this devastating hematologic complication, focusing on the importance of early recognition, as most patients achieve complete recovery with appropriate treatment. Key Points: Thrombotic thrombocytopenic purpura (TTP) was originally excluded from previous reviews of hematologic immune‐related adverse events; however, several cases have been reported in the past 2 years in patients treated with either single agent or combination of cytotoxic T‐lymphocyte–associated antigen 4 and the programmed cell death receptor 1 (PD‐1) or the PD‐1 ligand inhibitors. Although rare, TTP is a life‐threatening condition that could be challenging to diagnose, and early recognition is key as delayed treatment is associated with significant increase in mortality. The pathophysiology of immunotherapy‐induced TTP is likely related to autoimmune inhibition of ADAMTS13; the addition of prednisone and rituximab to urgent plasmapheresis appears to be effective and should be part of the up‐front management for these patients. Abstract : Immunotherapy is frequently associated with autoimmune complications in cancer patients but few cases of thrombotic thrombocytopenic purpura (TTP) have been reported. This article presents the first case of nivolumab‐associated TTP in a woman with stage IIIc anal carcinoma.